Phthalonitrile‐containing poly(amide imide)s with nanoactuation properties. Issue 2 (20th July 2012) - Hamciuc, Elena; Hamciuc, Corneliu; Carja, Ionela‐Daniela; Vlad‐Bubulac, Tachita; Ignat, Mircea
Abstract A series of aromatic poly(amide imide)s containing pendant phthalonitrile groups was prepared by solution polycondensation reaction of 4, 4′‐diamino‐4″‐(3, 4‐dicyanophenoxy)triphenylmethane, 1, or of different amounts of 1 and 1, 3‐bis(4‐aminophenoxy)benzene, with a fluorinated imide diacid chloride, 2, 2‐bis[N‐(4‐chloroformylphenyl)phthalimidyl]hexafluoroisopropane. The polymers were easily soluble in polar organic solvents, such as N‐methyl‐2‐pyrrolidone, N, N‐dimethylacetamide, N, N‐dimethylformamide, and dimethylsulfoxide. They can be cast from solutions into thin flexible films showing nanoactuation properties in the range of 120–450 nm, depending on the nitrile group content, when an electric voltage is applied on their surface. Electrical insulating properties of the polymer films were evaluated on the basis of dielectric permittivity and dielectric loss and their variation with the frequency and temperature. The values of the dielectric permittivity at 10 kHz and 20°C were in the range of 3.01–3.43. All polymers exhibited high thermal stability, decomposition temperature being above 420°C. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers